Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Jasa Audit Eksternal Pada Koperasi Di Jawa Timur - Lisa, Oyong (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2013)
The result of analysis showed that the members, cooperation scale, and total liabilities of simultaneous impact significant to service requisition audits external. Members partially impact significant to service requisition audits external, meanwhile cooperation scale and total liabilities not significant ascendant to service requisition audits external. Financial statement that auditing to have impact that advantages to divide efficiency and employee integrity, since what does he worked and reported by employee all this time was tested accuracy and its naturalness. Reporting that is audited will give result at least in fix accounting process fault and reduces estimation fault possible revaluation by employee. Other impact for management is base that check external auditor gets to give kind of autosuggestion to fix operation and up to greater operation efficiency.